Fluid Reading Practice: On the Queer Potential of Studying Nonhuman Animals - Irni Sari (Lectito, 2022)
This paper contributes to recent discussions about the relevance of the natural sciences and nonhuman animals in feminist theory by drawing from feminist debates on the queer potential of studying nonhuman animals. The paper discusses readings on the intertwining of scientific accounts of nonhuman animals and politics; how different nonhuman animal bodies have enabled various conceptualisations of sex and physical intimacy and have been enmeshed in the politics of sex; and how to read the relevance of accounts of the diversity of nonhuman animal sex(es) for feminist endeavours. These discussions contribute to an exploration of ‘fluid reading’, a feminist reading practice which draws inspiration from and moves with both new materialisms and poststructuralisms. The paper proposes that not only mood is important in feminist reading practices but also movements and flows.